2013
DOI: 10.1111/jvp.12034
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic and intestinal CYP3A expression and activity in broilers

Abstract: Cytochrome P450 is involved in drug metabolism. Subfamily CYP3A shows a degree of similarity across different animal species. However, little information is available about its expression and activity in broiler chickens. A RT-PCR method was developed for the quantification of CYP3A37 expression in the liver and small intestine of broilers. A higher expression in the jejunum was observed compared with that in the ileum. In the liver, a significantly lower expression compared with that in the jejunum was notice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Previously it has been shown that the elution of intestinal samples with EDTA resulted in the highest CYP450 activity when compared to the mucosal scraping method 68 . Furthermore, in the comparison between the EDTA elution method and the mincing method, it was shown that the latter resulted in higher enzymatic activities and more reproducible results 69 . Hence the mincing method was used in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Previously it has been shown that the elution of intestinal samples with EDTA resulted in the highest CYP450 activity when compared to the mucosal scraping method 68 . Furthermore, in the comparison between the EDTA elution method and the mincing method, it was shown that the latter resulted in higher enzymatic activities and more reproducible results 69 . Hence the mincing method was used in the current study.…”
Section: Discussionmentioning
confidence: 99%